REVEALING TRANCENDENTAL MEANING BEHIND THE OMAH DUDUR ARCHITECTURAL IN URUT SEWU, GRABAG, PURWOREJO, CENTRAL JAVA, INDONESIA - Satrio HB Wibowo; Sudaryono Sudaryono; E. Pradipto (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2017)
Omah dudur was discovered as a typical house in Urut Sewu, Purworejo-Kebumen, Central Java, Indonesia. By this research, it was found that Omah Dudur is considered as a manifestation of universe of human, god and nature as well as a pusaka (heirlooms). It is believed that interrelation among the three universes will influence to the successes and failures of occupants life. As a pusaka (heirlooms) which has the power and strength of wahyu, the omah dudur spiritually should be offered by certain ritual in the regular sacred time. Methodologically, this research implies Husserl’s paradigm phenomenology (1965) with the naturalistic framework of Egon G Lincoln and Guba (1985). Result of the study should be contributed to the knowledge of local concepts of typology of traditional and vernacular Javanese architecture. Keywords: omah dudur, wahyu, contextual transcendent, pusaka.